Readiness Factors of Chiang Mai City to Support Sustainable and Livable City Long-Stay Tourism - Auttarat, Sudarat; Poonsukcharoen, Nivej (Journal of Architectural/Planning Research and Studies (JARS), 2022)
In Thailand, both the public and private sectors have focused extensively on a policy of long-stay tourism as a channel for development. Such a policy aims to encourage capability of service and quality of physical factors that could support foreign long-stay tourists in Thailand. Chiang Mai is one of the cities in Thailand that pays particular attention to support long-stay tourism, as the city has the largest number of a long-stay tourists in Northern Thailand. This study examined readiness factors of Chiang Mai City that could support sustainable and livable long-stay tourism and proposed guidelines for improvement. The research tools were in-depth interviews and brainstorming discussions with key experts and stakeholders. The research identified 17 potential factors that could support Chiang Mai’s effort to be a long-stay city, but only 4 factors were confirmed to be at a high level of readiness. These 4 factors consisted of 1) effective disaster management system, 2) basic and sufficient elements to serve long-stay tourists, 3) cultural heritage preservation that illustrates a history and understanding of the traditional way of life, and 4) reasonable and affordable cost of living. This study also proposed some concrete preparedness guidelines for Chiang Mai City to support the transition to a sustainable and livable long-stay city.